Evaluation of Office Management Expertise Program in Improving Work Readiness of SMK Islam Krembung Students Using Multiple Intelligences Model - YAQIN, Mohammad Nurul; SUWADI, Suwadi (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study aims to evaluate the effectiveness of the Office Management Expertise Program at SMK Islam Krembung in improving students' work readiness. In the evaluation process, the Multiple Intelligences Model approach developed by Howard Gardner was used.Methodology:This model allows for in-depth analysis of various types of intelligence relevant to the field of office administration, including linguistic-verbal, logical-mathematical, interpersonal, and other intelligence. The research method applied is evaluative, with data collection through observation, tests, and interviews.Findings:The results of the study indicate that the Multiple Intelligences-based approach provides more comprehensive insight into students' work readiness, as well as identifying aspects of intelligence that need to be strengthened in the curriculum and teaching methods.Implication:This approach provides a more comprehensive understanding of the different types of intelligence relevant to the world of work, allowing for more integrated and tailored teaching to students' needs. These findings are expected to provide recommendations for the development of expertise programs that are more effective and responsive to the demands of the world of work.